Factors that Influence the Credit Risk of Peruvian Microfinance Institutions: Municipal Savings and Credit Banks - Toledo Concha, Emerson (2022)
The microfinance industry in Peru is constantly seeking to identify the factors that allow it to have better management and control its level of delinquency, since in recent years there has been a significant increase in provisions, reflected in the decrease in the economic results of an important group of microfinance institutions. The objective of this research work is to analyze whether the management decisions in reference to the size of the average portfolio per debtor and the total number of debtors per employee were determining factors that impacted the credit risk of the municipal savings and credit banks in Peru between the years 2016-2019. This research has a quantitative approach, for whose purpose the historical data information has been processed using a statistical tool (CRISP-DM), as well as data mining techniques and the use of logistics regressions. In addition, the results have been corroborated by experts in the microfinance sector. The relevance of this research lies in allowing the making of better strategic decisions that lead to a better control of the delinquency indicator and, therefore, to the improvements of results by this group of institutions.